Evidence-based therapy for heart failure - Deedwania, Prakash C; Carbajal, Enrique (The Medical clinics of North America, 2012)
Heart failure (HF) is a major public health problem associated with increased morbidity and mortality. As the US life expectancy increases and the population ages, the overall prevalence of HF will continue to escalate. The increasing use of effective selective therapies such as neurohormonal blockade in the treatment of patients with HF has led to considerable improvement in their prognosis. During the past several decades, some studies have demonstrated the benefits of treatment; based on the evidence available from these studies, various national and international guidelines have specific recommendations for the evidence-based therapy with these drugs in patients with HF.